2021
DOI: 10.1080/21580103.2020.1866089
|View full text |Cite
|
Sign up to set email alerts
|

Effects of elevated atmospheric CO2 on rhizosphere microbial community of Pinus densiflora (Korean red pine)

Abstract: The concentration of atmospheric CO 2 is increasing largely owing to human activities. Although it is well established that elevated CO 2 (eCO 2 ) stimulates plant growth and primary productivity, the effect of eCO 2 on soil microbial communities remains poorly understood. In this study, we aimed to examine the effects of eCO 2 on the taxonomical diversity, composition, and structure of rhizosphere microbial communities of Korean red pine (Pinus densiflora) through next-generation sequencing (NGS) of 16S rRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Pine trees are very important as they represent one of the dominant species of global forests as they provide food and cover for small animals and birds. Studies on several pine species have revealed the vulnerability of these species to abiotic stress, especially drought stress (Mitchell et al, 2013;Quan and Ding, 2017;Asbjornsen et al, 2021;Lee et al, 2021b). However, Korean pine species show seasonal variations in their drought response (Song et al, 2020;Lee et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…Pine trees are very important as they represent one of the dominant species of global forests as they provide food and cover for small animals and birds. Studies on several pine species have revealed the vulnerability of these species to abiotic stress, especially drought stress (Mitchell et al, 2013;Quan and Ding, 2017;Asbjornsen et al, 2021;Lee et al, 2021b). However, Korean pine species show seasonal variations in their drought response (Song et al, 2020;Lee et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%